MENYOROTI POLIGAMI BAGI PNS DALAM KAJIAN PERUNDANG-UNDANGAN HUKUM KELUARGA ISLAM - Nurulia Shalehatun Nisa; Maulana Umar Inamul Hasan; Arum Al Fakih (TAHKIM, 2022)
The provisions regarding polygamy in Indonesia have been regulated in several laws, including Law Number 1 of 1974, Government Regulation Number 9 of 1975, special provisions of Government Regulation Number 10 of 1983 and Government Regulation Number 45 of 1990, as well as the Compilation of Islamic Law. This paper aims to map the concept and status of polygamy that already exists in various laws and regulations in Indonesia. Researchers try to contextualize the practice of polygamy carried out by Civil Servants and their relevance to applicable laws. This paper is the result of a simple qualitative research that refers to the theory of functional structural analysis by Emile Durkheim. The concept and substance of polygamy in Indonesian legislation does not differ much, that is, it regulates the procedures and requirements for polygamy and aims to guarantee rights and justice for anyone involved in polygamous marriages. But today, these laws are no longer relevant enough to guarantee justice. Researchers offer solutions for the realization of the ideal polygamy legislation in Indonesia. In addition to the need for rules that cover supervisory procedures that must be enforced, it is also necessary to have an understanding that is imprinted on each individual to live up to the basic purpose of the law being created, namely to achieve justice.Keywords: Polygamy, legislation, Civil Servants, justice.